Inspired by Bakhtin : dialogic methods in the humanities - Freise, Matthias, 1957- (Studies in comparative literature and intellectual history, 2018)
The revisionist approach in this book, based on Mikhail Bakhtin's work, traces the search for common and specific grounds of the humanities, beginning with psychologism through hermeneutics and semiotics up to the present state of self-annihilation. As an alternative, the book seeks to define humanities as the examination of relationships, which offers an array of refreshing perspectives on each field discussed.